How effective are EFL software for English learning in Vietnamese education context? - Thu Huong, Pham Thi; Van Long, Nguyen (Opción, 2019)
This study investigated the extent to which English Foreign Language software programs recently used to support teaching and learning English at the colleges and universities in the Center of Viet Nam. The five most widely used EFL (English as a Foreign Language) software programs or webpages of which technological features and pedagogical features were evaluated according to an interactive approach. Results indicated that Life and DynEd are the two EFL software programs having the biggest potential to develop learners’ EFL skills. In conclusion, the individualized-learning features of these two software programs were highly evaluated and this, in turn, promoted English development in EFL learners.